Affective touch in the context of development, oxytocin signaling, and autism - Li, Qin; Zhao, Weihua; Kendrick, Keith M. (Frontiers in Psychology, 2022)
Touch represents one of our most important senses throughout life and particularly in the context of our social and emotional experiences. In this review, we draw on research on touch processing from both animal models and humans. Firstly, we briefly describe the cutaneous touch receptors and neural processing of both affective and discriminative touch. We then outline how our sense of touch develops and summarize increasing evidence demonstrating how essential early tactile stimulation is for the development of brain and behavior, with a particular focus on effects tactile stimulation in infant animals and pediatric massage and Kangaroo care in human infants. Next, the potential mechanisms whereby early tactile stimulation influences both brain and behavioral development are discussed, focusing on its ability to promote neural plasticity changes and brain interhemispheric communication, development of social behavior and bonding and reward sensitivity through modulation of growth factor, oxytocin and opioid signaling. Finally, we consider the implications of evidence for atypical responses to touch in neurodevelopmental disorders such as autism spectrum disorder and discuss existing evidence and future priorities for establishing potential beneficial effects of interventions using massage or pharmacological treatments targeting oxytocin or other neurochemical systems.